The cultural representation in EFL textbook of merdeka curriculum - Khoeriah, Anisa; Hidayat, Didin Nuruddin; Alek, Alek; Mulyati, Yatni Fatwa (SEAN Institute, 2024)
The study aims to investigate the cultural representation of the EFL Textbook mandated by the Indonesian government in the Merdeka Curriculum for 10th-grade students. The frameworks used for the analysis are Moran's (2001) theory of five dimensions of culture (products, practices, perspectives, communities, and persons) and Chao's (2011) theory of cultural categories (target culture, source culture, international culture, intercultural communication, and universality across culture). Qualitative content analysis is used as the research method. The study's primary data is an English textbook titled Bahasa Inggris: Work in Progress, published by the Indonesian Ministry of Education and Culture (2022) as delivered in implementing the Merdeka Curriculum. The results show that the represented cultural dimensions in the textbook are products (34%), practices (31%), persons (15%), perspectives (13%), and communities (7%). Whereas, for the cultural categories, the result shows that the textbook represents the international culture (32%), source culture (29%), universality across cultures (20%), target culture (16%), and intercultural interaction (3%). Therefore, all cultural dimensions and cultural categories are represented in the textbook with different frequencies. However, the textbook needs improvement regarding the consistency of the cultural dimensions and categories.